Viability of Increased Vessel Size in Tramp Shipping : a Case Study in the Baltic Sea Region - Lehtinen, Ninni (My University, 2019)
The tramp shipping market is characterized by multiple small players acting as price takers in a competitive environment with highly fluctuating and unpredictable demand. To cope with small margins, increasing vessel size with the aim to reach economies of scale has been a trend of the shipping industry for years. The thesis investigates the viability of increased vessel size in tramp shipping from the viewpoint of a t/c owner that further offers transport services in the tramp shipping market. The t/c owners operating are is mainly the Baltic Sea Region, which is interesting for the study as traditionally shipping in the Baltic Sea Region has been performed to some extent smaller vessel as compared to deep-sea shipping. The thesis examines both profitability and differences in the determinants of profitability of two different size vessels (DWCC 8300 mts & 2850 mts) that have completed the same voyages. The thesis is performed as a case study that takes form of a nomothetical approach. Data sources used include final disbursement accounts, voyage data from the company’s data management system, statements of facts from port calls as well as information received from captains. Based on the information, scenarios have been produced to analyse the effect different changes to the t/c owner’s profitability and its determinants. The findings include that daily profit improves with growth in vessel size on all the compared voyages and conducted scenarios. It is also found that the profit made by the bigger vessel is more prone to changes in bunker price, freight rate, time spent at port and ballast voyage length alterations, implying that operating the bigger vessel is much riskier. It was also found that if the cargo quantity of the bigger vessel reduces to abt. 65-90 % depending on voyage, the daily profit of the bigger vessel can no longer outrun that of the smaller one. Therefore, it is of importance for the t/c owner can find full cargoes from the market in order to reach for economies of scale with its bigger vessel.
Keywords: tramp shipping, bulk shipping, short-sea shipping, economies of scale, profitability